PENGARUH ORDER EFFECT DAN POLA PENGUNGKAPAN DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Barbara Gunawan; M. Hendra Yusuf (Universitas Trunojoyo Madura, 2012)
The aims of this study are to examine the influence of order effects on the investment judgment, and also to examine how recency effect influence the step by step (SbS) pattern and end of sequence (EoS) pattern related to the assessment of the company's decision to use company’s financial information. Participants in this study are 84 students majoring in accounting of private universities in Yogyakarta.The results indicate that order effect influence in a different way on the investment decision-making. Both step by step (SbS) pattern and end of sequence (EoS) pattern influence differently on decision-making as well. Recency effect happened only in step by step (SbS) pattern. The results also provide evidence that no effect of recency affect in end of sequence (EoS) pattern.